2020
DOI: 10.3390/life10060098
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Study of the Mechanism of Binding of the N-Terminal Region of α Synuclein to Synaptic-Like Membranes

Abstract: The membrane binding by α-synuclein (αS), a presynaptic protein whose aggregation is strongly linked with Parkinson’s disease, influences its biological behavior under functional and pathological conditions. This interaction requires a conformational transition from a disordered-unbound to a partially helical membrane-bound state of the protein. In the present study, we used enhanced coarse-grained MD simulations to characterize the sequence and conformational determinants of the binding to synaptic-like vesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 56 publications
2
20
0
Order By: Relevance
“…In order to characterize new mechanistic aspects of the double-anchor mechanism ( Fusco et al, 2016b ), we studied the modes of binding the region spanning residues 65–97 of αS (αS 65–97 ) with DOPE:DOPS:DOPC lipid bilayers mimicking the lipid composition of SV, using CG MD simulations based on a modified version of the Martini 3 force field ( Navarro-Paya et al, 2020 ). In this model, the motions of the backbone atoms are restrained to adopt two main conformational basins, respectively, accounting for extended-disordered and helical conformations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to characterize new mechanistic aspects of the double-anchor mechanism ( Fusco et al, 2016b ), we studied the modes of binding the region spanning residues 65–97 of αS (αS 65–97 ) with DOPE:DOPS:DOPC lipid bilayers mimicking the lipid composition of SV, using CG MD simulations based on a modified version of the Martini 3 force field ( Navarro-Paya et al, 2020 ). In this model, the motions of the backbone atoms are restrained to adopt two main conformational basins, respectively, accounting for extended-disordered and helical conformations.…”
Section: Methodsmentioning
confidence: 99%
“…The GROMACS 4.6.7 package ( Abraham et al, 2015 ) and a modified version ( Navarro-Paya et al, 2020 ) of the Martini 3 force field ( Bruininks et al, 2019 ) (see below) were employed in CG simulations of membrane-binding binding by the region 65–97 of αS (αS 65–97 ). The composition of the synaptic-like membrane employed in this study recalls previous experimental ( Fusco et al, 2016b ) and in silico ( Navarro-Paya et al, 2020 ) investigations and includes DOPE, DOPS, and DOPC lipid molecules mixed at a 5:3:2 (w/w) ratio (167 lipids in total). The protein was modeled with neutral termini, and the membrane component was generated using the Martini tool insane.py ( Wassenaar et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, moving beyond the general prediction of order or disorder, computational methods-specifically, molecular dynamics simulations-can be used to supplement experimental results and obtain more detailed structural insights. This has the benefit of allowing the probing of systems and timescales which are not (easily) experimentally accessible, and can therefore be a valuable tool in the study of IDPs [92][93][94]. Care must be taken in such studies, however, as it has been shown that results of such MD studies can depend strongly on how the simulation was set up.…”
Section: Computational Methods For Sequence-based Prediction Of Disordermentioning
confidence: 99%
“…The results showed that this protein relies on a conformational selection mechanism to recognise the correct molecular partners. Coarse-grained MD simulations were also used by Navarro-Paya et al [ 6 ] to characterise the fundamental binding of α-synuclein (αS), a central IDP whose aggregation is associated with Parkinson’s disease, to synaptic membranes. This protein is completely disordered in the cytosol but undergoes disorder-to-order transition upon binding with biological membranes.…”
mentioning
confidence: 99%